Skip to main content

Mathematical Analysis

Section 1.1 Binary Operations and Fields

“I never say of an operation that it is without danger.”
―August Bier

Definition 1.1. Binary Operation.

A binary operation on a set \(X\) is a function from \(X × X\) into \(X\text{.}\)

Definition 1.2. Binary Operation Properties.

  • A binary operation on a set \(S\) is commutative if \(a*b=b*a\) for all \(a,b\in S\text{.}\)
  • A binary operation on a set \(S\) is associative if \((a*b)*c=a*(b*c)\) for all \(a,b,c\in S\text{.}\)
  • An element \(e\) is called an identity if \(e * x=x=x * e\) for all \(x\in S\text{.}\)
  • An element \(y\) is called an inverse of \(x\) if \(y * x=e=x*y\text{.}\)

Definition 1.3. Field.

A field is a set \(F\) with two operations
  • addition: \(F\times F\rightarrow F:(x,y)\mapsto x+y\)
  • multiplication \(F\times F\rightarrow F: (x,y)\mapsto xy\) (or \(x\cdot y\))
such that
  1. \(\displaystyle (a+b)+c=a+(b+c)\,\forall\,a,b,c\in F\)
  2. \(\displaystyle a+b=b+a\,\forall\, a,b,\in F\)
  3. \(\exists 0\in F\) st \(a+0=a=0+a\,\forall\, a\in F\) (exercise: 0 is unique)
  4. \(\forall\,a\in F\exists -a\in F\) such that \(a+(-a)=0=(-a)+a\)
  5. \(\displaystyle (ab)c=a(bc)\,\forall\, a,b,c\in F\)
  6. \(\displaystyle ab=ba \,\forall\, a,b,\in F\)
  7. \(\exists 1\in F\) such that \(\forall a\in F\, a1=1=1a\) (\(1\neq 0\text{,}\) exercise to show \(1\) unique)
  8. \(\forall\,a\in F\setminus\{0\},\exists a^{-1}\) such that \(aa^{-1}=1=a^{-1}a\) (exercise show \(a^{-1}\) unique)
  9. \(\displaystyle a(b+c)=ab+ac\,\forall\, a,b,c\in F\)
  10. \(\displaystyle (a+b)c=ac+bc\,\forall\, a,b,c\in F\)

Definition 1.4. Subtraction, Division.

Let \(x\) and \(y\) be elements of a field \(F\text{.}\) We define binary operations \(-\) and \(÷\) on \(F\) such that \(x-y=x+(-y)\) and \(x÷y=x\cdot\frac 1y\text{.}\)

Convention 1.5.

Following the usual convention, we write \(\frac xy\) instead of \(x÷y\text{.}\)
\(x·(0 + 0) = x·0\) by axiom 4. On the other hand \(x·(0 + 0) = x·0 + x·0\) by axiom 11. Thus \(x·0 = x·0 + x·0\text{.}\) Now
\begin{equation*} x·0 + [–(x·0)] = (x·0 + x·0) + [–(x·0)] \end{equation*}
Again using axiom 5 and axiom 2, we have \(0 = x·0 + 0\) and so by axiom 4 we have \(0 = x · 0\text{.}\)